Lymphoepithelial Cyst of the Pancreas: A Challenging Differential Diagnosis among Cystic Pancreatic Tumors - Milanetto, Anna Caterina; Orvieto, Enrico; Sperti, Cosimo; Pasquali, Claudio (JOP. Journal of the Pancreas, 2013)
Context First described by Luchtrath and Schriefers in 1985 [1], lymphoepithelial cysts (LECs) of the pancreas are rare true benign cystic tumors of uncertain etiology (0.5% of all pancreatic cysts). They are found mainly in middle-aged males in the tail of the pancreas (size range: 2-10 cm). The challenging preoperative differential diagnosis of pancreatic LECs is among pseudocysts, cystic neoplasms and intraductal carcinomas. Case report During follow up for prostatic cancer, a 66-year-old man presented as an incidental finding at abdomen CT scan, a multiloculated cystic lesion (8x6 cm), located between duodenum and pancreatic head, with a solid component in its lower side, without contrast enhancement. MRI confirmed the lesion, suspected to be a mucinous tumor non communicating with the Wirsung duct. A pancreatic EUS showed a inhomogeneous cystic mass of the head of the pancreas, which had internal septa and a solid component. The amylase level in the cystic fluid content was 84 U/L, and CEA and CA 19-9 levels were 301 μg/L and 76,579 kU/L, respectively. Histology of the solid component was inconclusive. A 18FDG-PET was negative for pancreatic malignancy. Blood tests showed a severe increase of creatinine and urea levels, because the patient had an acute renal failure due to the prostatic cancer, and serum CEA and CA 19-9 levels were 2.7 μg/L and 81 kU/L, respectively. After renal function normalization, with the suspicion of a mucinous cystic neoplasm (MCN), the patient underwent surgery. The mass had a tight-elastic thickness and seemed not to involve the pancreatic parenchyma, so a resection of the lesion was performed. The post-operative course was uneventful. Histology revealed a cystic lesion (8x4 cm) containing yellowish fluid, lined by a stratified squamous epithelium with focal sebaceous differentiation, and surrounded by lymphoid tissue. The patient is well and asymptomatic three months after surgery. Conclusion LECs should be considered in the differential diagnosis of cystic pancreatic tumors, whenever a large, well-defined solid or cystic peripheral pancreatic lesion is found. Imaging findings of LECs are non-specific, so surgical resection with pathological examination of the cyst is the gold standard for diagnosis. Cytology from EUS-FNA can help to distinguish LECs from cystic neoplasms.